2015
DOI: 10.1111/bjet.12358
|View full text |Cite
|
Sign up to set email alerts
|

Quality parameterization of educational resources from the perspective of a teacher

Abstract: Objective assessment of the quality of available educational resources presupposes the existence of specific quality standards and specific evaluation tools which consider the specificities of digital products with educational ambitions. The study presents the results of research conducted on a representative sample of teachers who commented on issues related to the importance of measuring the quality of available educational resources and the hierarchy of the key characteristics of such devices. The research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…In the e-learning environment, the teachers identified e-learning content as the key and fundamental characteristics of such resources from a user's perspective (Karolčík et al, 2017). In our research, we argue that 'quality' means the level of perceived intention use of LMS throughout the analysis of e-learning resources (content reliability, responsiveness and knowledge contribution) using the ServQual Model adapted (Ameen et al, 2019;Parasuraman et al, 1988).…”
Section: Quality Evaluation Modelsmentioning
confidence: 80%
See 4 more Smart Citations
“…In the e-learning environment, the teachers identified e-learning content as the key and fundamental characteristics of such resources from a user's perspective (Karolčík et al, 2017). In our research, we argue that 'quality' means the level of perceived intention use of LMS throughout the analysis of e-learning resources (content reliability, responsiveness and knowledge contribution) using the ServQual Model adapted (Ameen et al, 2019;Parasuraman et al, 1988).…”
Section: Quality Evaluation Modelsmentioning
confidence: 80%
“…Recent studies showed that technological factors such as perceived usefulness, ease of use, and social norms impact students' platform usage intent (Granić & Marangunić, 2019;Khechine et al, 2020;Scherer & Teo, 2019). Some studies explore the quality of materials and e-learning resources using methodological guidelines as an important factor for explaining LMS adoption from students' perspective (Karolčík et al, 2017;Naveh et al, 2010;Uppal et al, 2018).…”
Section: Practitioner Notesmentioning
confidence: 99%
See 3 more Smart Citations